Tudásközvetítés a 17. századi unitárius prédikációirodalomban: Caspar Sibelius prédikációinak fordítása az Ms. U. 584 jelzetű kéziratban - Hajdu, Ildikó (Studia Litteraria, 2026)
The paper analyses the Ms. U. 584 of the Academic Library of Cluj-Napoca. I examine the attribution of the manuscript and argue for the correction of the author’s name by linking to him another manuscript from the same collection (call number: Ms. U. 659). After presenting the known biographical data about the newly identified author (including books with his inscriptions), in the second part of the paper I investigate the sources of the sermons and argue that 41 sermons out of altogether 112 in the Ms. U. 584 are translations and copies from Caspar Sibelius’s two sermon collections, the Fraenum iuventutis (1639) and the Humilitas Davidica (1640). Finally, I examine the possible reasons and routes of the reception of Sibelius in the Transylvanian Unitarian community in the seventeenth century.